The Blue Economy an emerging economy for coastal nations - Diwan, A D; Harke, S N (Indian Farming, 2018)
Blue economy is considered as a holistic development based upon the optimum and efficient utilization of oceanic resources without compromising on the sustainability. Coastal nations whose economic developments depend on the marine resources particularly the small island countries, they should follow this kind of approach. Even the advanced countries like USA, Canada and Australia consider the Blue economy as the new source of economic growth especially after the recession in overall economy in recent past. By and large, all coastal nations are of the view that the Blue Economy is an important sector of their economies which should get priority in their respective legislation and action plan for ocean development. Many coastal countries including India consider the blue economy as a strategic economic sector for achieving substantial overall economic growth and other developmental objectives. Blue Economy broadly covers living resources such as fisheries and aquatic plants and non-living resources such as polymetallic nodules, cobalt crust, rare earth metals and other minerals, oil and gas, port and shipping, coastal tourism, marine biotechnology, marine commerce and so on. Of those, capture fishery, oil and gas exploration, shipping, coastal tourism etc. are the traditional sectors whereas multi-species aquaculture, fish processing, marine derived bioproducts, seaweed products, coastal tourism and high-tech marine products are some of those emerging sectors of Blue economy. Besides their current level of contribution, there is immense potential existing in the above mentioned sectors for diversification and industrial applications.